Pengaruh Daya Beli Masyarakat Terhadap Kenaikan Harga Bahan Pokok Di Wilayah Kota dan Kabupaten Pekalongan - Gunawan Aji; Mohammad Nur Zein; Nabila Oktavianti; Hasna Alifa Rosyada (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
For example, egg prices peaked in April 2023, increasing by 2,46%. This data was obtained from the Badan Kebijakan Perdagangan (BKPerdag). This was triggered by the large public demand for eggs during April. This research used 10 research subjects who were people in Pekalongan City and Regency. Researchs also include literature studies used as sources in developing this research, such as books, websites, and research journals. This research aims to determine the opinions, suggestions, and input from the public, both traders and sellers, regarding the increase in prices of basic commodities on the market. It is hoped that the research will provide benefits for readers and related parties and provide insight into the future. The results of this research show that price pressure in the market is quite high, wages are aligned with basic needs, there is stability in the prices of basic needs, and there is an increase in the price of basic needs over a certain period.